THE EFFECT OF WEBSITE QUALITY, PRICE AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN BUKALAPAK E-COMMERCE (CASE STUDY ON MALIKUSSALEH UNIVERSITY STUDENTS) - Alfaridho; Chalirafi; Mariyudi; Agustinawati (RADJA PUBLIKA, 2024)
This study aims to determine how the influence of website quality, price and service quality on Bukalapak e-commerce customer satisfaction in Malikussaleh University students. The data used in this study was primary data obtained by distributing questionnaires to 96 students who used Bukalapak. The questionnaire trial consisted of a validity test and a reliability test using Cronbach's Alpha method. The classical assumption test uses the normality test, the multicollinearity test and the heterokedasticity test. Test the hypothesis using t-test (partial), F-test (simultaneous), and coefficient of determination R2. The data analysis technique used is multiple linear regression using the help of SPSS software version 26. The results showed that the website quality variable did not affect the satisfaction of Bukalapak e-commerce customers in Malikussaleh University students. While the price and service quality variables partially have a positive and significant effect on Bukalapak e-commerce customer satisfaction in Malikussaleh University students. Meanwhile, the test results simultaneously show that website quality, price and service quality simultaneously affect the satisfaction of Bukalapak e-commerce customers in Malikussaleh University students. The results of the coefficient of determination test found that Bukalapak e-commerce customer satisfaction in Malikussaleh University students was influenced by website quality, price and service quality by 21.6%, the remaining 78.4% was influenced by variables outside this study.